Effect of Nano Powder on Mechanical and Physical Properties of Glass Fiber Reinforced Epoxy Composite - Abdul-Hussein, Aseel Basim; Hashim, Fadhel Abbas; Kadhim, Tamara Raad (Al-Khwarizmi Engineering Journal, 2017)
Fiber reinforced polymer composite is an important material for structural application. The diversified application of FRP composite has taken center of attraction for interdisciplinary research. However, improvements on mechanical properties of this class of materials are still under research for different applications. In this paper we have modified the epoxy matrix by Al2O3, SiO2 and TiO2 nano particles in glass fiber/epoxy composite to improve the mechanical and physical properties. The composites are fabricated by hand lay-up method. It is observed that mechanical properties like flexural strength, hardness are more in case of SiO2 modified epoxy composite compare to other nano modifiers, were physical properties like density, water absorption are more in case of TiO2 modified epoxy composite. This may be because of smaller particle size of silica compare to others.